2008
DOI: 10.1080/09273940802184190
|View full text |Cite
|
Sign up to set email alerts
|

Endophthalmitis Caused byCitrobacterSpecies

Abstract: Despite treatment with appropriate antibiotics, Citrobacter endophthalmitis can be associated with a poor visual outcome. Early detection and management may improve the final visual outcome and prevent the possibility of evisceration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…Citrobacter sp. are rare causes for ocular infections [ 3 , 6 ], and are rarely isolated in patients with bacterial keratitis [ 2 , 7 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Citrobacter sp. are rare causes for ocular infections [ 3 , 6 ], and are rarely isolated in patients with bacterial keratitis [ 2 , 7 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Like other virulent Gram-negative organisms, endophthalmitis caused by Citrobacter species can be associated with a poor visual outcome in spite of maximal treatment. Chen et al [8] reported 6 cases of endophthalmitis caused by Citrobacter species, of which 4 cases were caused by Citrobacter freundii and 2 cases were caused by Citrobacter koseri . Final visual acuity was limited to no light perception in 5 eyes among 6 cases, although maximal medical and surgical treatment were undertaken after diagnosis of endophthalmitis.…”
Section: Discussionmentioning
confidence: 99%
“…Final visual acuity was limited to no light perception in 5 eyes among 6 cases, although maximal medical and surgical treatment were undertaken after diagnosis of endophthalmitis. However, in one case caused by Citrobacter koseri , the patient was able to achieve 20 / 30 vision, according to their report [8]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas endophthalmitis occurs at an average annual incidence of 5 in 10,000 hospitalized cases, only 2% to 15% are endogenous. 14 Other infrequently encountered organisms include Citrobacter, 15 Aeromonas hydrophilia, 16 and nontuberculous mycobacteria. Endogenous endophthalmitis is associated with several medical conditions such as diabetes, lymphoproliferative disease, malignancy, immunosuppression, parenteral alimentation, recent extended surgical procedure, alcoholism, or intravenous drug abuse.…”
Section: Clinical Settings Causative Organisms and Epidemiologymentioning
confidence: 99%